Technologia informacyjno-komunikacyjna w zarządzaniu wiedzą niejawną w organizacji - Ziemba, Ewa (Information and Communication Technology in Tacit Knowledge Management in an Organisation, 2006)
The article aims at presenting selected issues that are related to the application of Information and communication technologies in tacit knowledge management. First, nature of tacit knowledge and its management is presented. Subsequent parts characterise Information technology tools that support searching for knowledge and its sources, and knowledge codifying, publishing and sharing. The article is concluded by pointing out that corporate portals are a platform that integrates information technology tools that support tacit knowledge management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 209-225